Keynes, Keynesians, and Monetarists - Weintraub, Sidney, 1914-1983; Davidson, Paul, 1930-2024 (University of Pennsylvania Press, 1978)
New disorders require new polices, says economist Sidney Weintraub. In this book he draws together many of his shorter writings to deal with economic problems that have defied orthodox monetary and fiscal remedies. Weintraub has long been noted for his vigorous criticism of both monetarist and Keynesian schools of thought for their failure to cope with disorders in our economy involving unemployment and inflation. Keynes, Keynesians, and Monetarists contains the original article on TIP, written in collaboration with Henry Wallich, outlining a tax-based incomes policy to combat inflation in an era of unemployment. This essay has been the focus of extended discussion in official quarters, among economics and in the public press.